PENGEMBANGAN MASASE OLAHRAGA UNTUK PEMANASAN BAGI ATLET PUTRI KLUB BOLAVOLI PERKASA JAYA BLITAR - Sebtian Kristin Anita Rohmawati; Mulyani Surendra; Sri Purnami (Jurnal Sport Science, 2016)
Abstract: This research aims to develop a sports massage to warm up on the sport volleyball as an alternative form of heating that is useful to help prepare the physical condition before training or competing. Expected results of this development is beneficial to women athletes volleyball club Perkasa Jaya Blitar. This research method refers to a model of the development of research and development (R & D) of Borg and Gall uses quantitative and qualitative analysis. Results of development in the form of a guide book then tested on a small group of test phase involving 10 women athletes volleyball club Perkasa Jaya Blitar obtain a yield of 88% so that it can be used and a large group trial involving 30 women athletes volleyball club Perkasa Jaya Blitar result by 90 , 5% so it can be used.Key word: sports massage, warming up, volleyball